2002
DOI: 10.1093/protein/15.1.35
|View full text |Cite
|
Sign up to set email alerts
|

An absolute requirement of fructose 1,6-bisphosphate for the Lactobacillus caseil-lactate dehydrogenase activity induced by a single amino acid substitution

Abstract: Lactobacillus casei allosteric L-lactate dehydrogenase (L-LDH) absolutely requires fructose 1,6-bisphosphate [Fru(1,6)P2] for its catalytic activity under neutral conditions, but exhibits marked catalytic activity in the absence of Fru(1,6)P(2) under acidic conditions through the homotropic activation effect of substrate pyruvate. In this enzyme, a single amino acid replacement, i.e. that of His205 conserved in the Fru(1,6)P(2)-binding site of certain allosteric L-LDHs of lactic acid bacteria with Thr, did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Multiple alignments with other reported l -nLDHs showed that all catalytically important residues (Arg 109, Asp 168, Arg 171, and His 195) were conserved in the B. coagulans SDM l -nLDH (Figure S1) [27]. Moreover, the amino acids involved in activation by fructose 1,6-bisphosphate (FDP) (Arg 173 and His 188) were also found in l -nLDH (Figure S1) [28]. The essential residues of d -nLDH (Arg 235, Glu 264, and His 296) were also conserved in the B. coagulans SDM d -nLDH (Figure S2) [29], [30].…”
Section: Resultsmentioning
confidence: 88%
“…Multiple alignments with other reported l -nLDHs showed that all catalytically important residues (Arg 109, Asp 168, Arg 171, and His 195) were conserved in the B. coagulans SDM l -nLDH (Figure S1) [27]. Moreover, the amino acids involved in activation by fructose 1,6-bisphosphate (FDP) (Arg 173 and His 188) were also found in l -nLDH (Figure S1) [28]. The essential residues of d -nLDH (Arg 235, Glu 264, and His 296) were also conserved in the B. coagulans SDM d -nLDH (Figure S2) [29], [30].…”
Section: Resultsmentioning
confidence: 88%
“…Recombinant LCLDH was expressed in Escherichia coli MV1184, and purified according to previous reports 23, 31. Type I crystals were prepared by the hanging drop vapor diffusion method at 25°C in 100 m M sodium citrate buffer (pH 4.4), 200 m M potassium sodium tartrate, and 1.6 M ammonium sulfate, and then transferred to a solution containing 1.8 M ammonium sulfate and 30% glycerol before flash‐cooling.…”
Section: Methodsmentioning
confidence: 99%
“…Oligodeoxynucleotide 5′‐GGT TAA CGT TGA TGC ACA ATC AGT CCA CGC TTA CAT CAT GGG‐3′ was used to replace Arg185 with Gln. Site‐directed mutagenesis was performed using the Gene Editor System from Promega, and expression and purification of the mutant LCLDH were performed by the same procedures as those used for the wild‐type enzyme 23…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations